A hydrodynamic basis for off-axis Brownian diffusion under intermediate confinements in micro-channels. (October 2021) - Kannan, Ananda Subramani; Mark, Andreas; Maggiolo, Dario; Sardina, Gaetano; Sasic, Srdjan; Ström, Henrik
Abstract: The mobility of a Brownian particle diffusing in a micro-channel is heterogeneous and spatially dependent on the surrounding hydrodynamic resistance fields. The positional asymmetry of such a diffusing particle leads to anisotropies in the observed diffusive behavior. In this paper, we probe such directionally varying diffusive behavior of a spherical nanoparticle diffusing at a location off-set from the centerline of a square micro-channel in a quiescent fluid. This investigation is carried out over varying degrees of intermediate hydrodynamic confinements. A coupled Langevin-immersed boundary method is used for these assessments. We observe that the co-axial diffusivity may be slightly enhanced during off-axis hindered diffusion when compared with a corresponding centerline diffusive behavior. We attribute this increased particle diffusivity to a reduced co-axial fluid resistance through a hydrodynamic basis derived using steady-state CFD solutions to the corresponding Stokes problem. For co-axial motion, the particle creates a recirculating flow pattern around itself when moving along the centerline, whereas it drags along the fluid in between itself and the wall when in close proximity to the latter. These contrasting flow behaviors are responsible for the unexpected enhancement of the co-axial diffusivity for some off-axis positions under intermediate hydrodynamic confinements. Graphical abstract: Highlights: Anisotropies in the hydrodynamic resistances during hindered diffusion probed. A coupled continuum mechanics-Langevin multiphase DNS ( LaIBM ) framework is used. LaIBM leverages the local hydrodynamics on-the-fly to estimate the ensuing diffusion. Co-axial diffusivity is enhanced during off-axis hindered diffusion. Enhancement in particle diffusivity due to a reduced co-axial fluid resistance.